Level of physical activity and sedentary behavior in children and adolescents diagnosed with cancer: A systematic review - Roussenq, Suellen Cristina; Gabellieri Hintz, Luisa; Dandara Rafael, Aline; Ramos, Ana Paula; Tapparello, Denise; Dubón, Ana Patricia; Zulianello dos Santos, Rafaella; Dias, Mirella; Benetti, Magnus (International Journal of Health Sciences, 2022)
Objective: The objective of the study was to examine already published evidence on the level of physical activity and sedentary behavior in children during and after treatment for cancer. And, thusly to verify if patients are following the recommendations of the World Health Organization, United States Centers for Disease Control and Prevention and American College of Sports Medicine. Methods: The platforms for searches were EBSCO, Web of Science and PubMed. The keywords used were physical activity, sedentary behavior, children or adolescents with cancer. Results: Found 4572 articles. 16 satisfied the eligibility criteria. The most children of whom had a low level of physical activity and a high level of sedentary behavior. Conclusions: We conclude that this population showed an increase in sedentary behavior. And, it was also observed that does not have specific recommendations for this population. Already, the recommendations used for the healthy children and for chronic patients are not ideal for this population. Therefore, it is demonstrated that specific recommendations must be created for this population.